2019
DOI: 10.1080/08870446.2018.1554184
|View full text |Cite
|
Sign up to set email alerts
|

Do smokers devaluate smoking cues after go/no-go training?

Abstract: Objective: Smoking is one of the leading public health problems worldwide. The inability to quit smoking may be the result of the amplified value of smoking-related cues and inhibitory control deficits. Previous research has shown that pairing substancerelated cues with no-go trials in go/no-go training reduces the value of these cues, an effect known as devaluation. The current experiment investigated the devaluation effect of go/no-go training on smoking-related cues, and compared this effect between smokers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 55 publications
2
20
0
6
Order By: Relevance
“…Keeping in mind the complexity of human sexual experiences, these initial results showing that motor-response inhibition can reduce the capacity of sexual stimuli to elicit both subjective and physiological sexual response do provide a promising avenue for future research. Such investigations focusing on problematic sexual behavior would align well with recent research on the utility of inhibition-based tasks for devaluing motivationally-relevant stimuli to address disorders of self-control in overeating (e.g., Veling, Lawrence, Chen, van Koningsbruggen & Holland, 2017), problem gambling (Stevens et al, 2015), and alcohol and drug abuse (e.g., Houben, Nederkoorn, Wiers, & Jansen, 2011;Scholten, Granic, Chen, Veling, & Luijten, 2019). Thus, our findings that inhibition can impact later stages of sexual response converge with other recent discoveries to support the possibility that the affective consequences of inhibition may be effectively utilized in a variety of clinical applications.…”
Section: Discussionsupporting
confidence: 56%
“…Keeping in mind the complexity of human sexual experiences, these initial results showing that motor-response inhibition can reduce the capacity of sexual stimuli to elicit both subjective and physiological sexual response do provide a promising avenue for future research. Such investigations focusing on problematic sexual behavior would align well with recent research on the utility of inhibition-based tasks for devaluing motivationally-relevant stimuli to address disorders of self-control in overeating (e.g., Veling, Lawrence, Chen, van Koningsbruggen & Holland, 2017), problem gambling (Stevens et al, 2015), and alcohol and drug abuse (e.g., Houben, Nederkoorn, Wiers, & Jansen, 2011;Scholten, Granic, Chen, Veling, & Luijten, 2019). Thus, our findings that inhibition can impact later stages of sexual response converge with other recent discoveries to support the possibility that the affective consequences of inhibition may be effectively utilized in a variety of clinical applications.…”
Section: Discussionsupporting
confidence: 56%
“…Analogical explanations are also present in alcohol dependence studies [13]. As for smoking, the devaluation effect was clearly demonstrated in the study by Scholten and colleagues [19]. They arranged GNG training in which participants were instructed to refrain from responding to smokingrelated pictures after a predetermined acoustic signal.…”
Section: Discussionmentioning
confidence: 82%
“…If the rst mechanism is dominant, the effects of training, if existent at all, should generalize on inhibitory control tasks that were not used during the training sessions. The second mechanism does not predict such transfer effects, but it should make the smoking-related stimuli less pleasant for participants who are asked to judge their value [19].…”
Section: Introductionmentioning
confidence: 94%
“…Moreover, the continuous withholding of responses to attractive cues may also produce conflicts and negative affect, that eventually may lead to devaluation of the initial targeted cues. To date, several studies have shown evidence for lower evaluations of trained No-Go compared to Go and/or untrained pictures, interpreted as evidence for devaluation (Chen et al, 2016(Chen et al, , 2018aHouben et al, 2012;Quandt et al, 2019;Scholten et al, 2019;Veling et al, 2013). However, some recent studies found that the effects of Go/No-Go training were smaller for rewarding stimuli and stronger for aversive or neutral stimuli (Chen et al, 2019;De Pretto et al, 2019), which is in apparent contrast with a cue-devaluation mechanism of rewarding cues.…”
Section: Go/no-go Tasksmentioning
confidence: 98%